(untitled) (International Journal of Physiotherapy, 2019)
Background: One of the main problems in a patient with Parkinson’s disease (PD) is recurrent falls. This paper aims to explore the nature of interventions which target the role of physiotherapy preventing fall in patients with PD. Methods: A scoping review was led dependent on Arksey and O’Malley. This paper-based on this structure to perceive intervention studies have been embraced in physiotherapy to prevent fall after Parkinson disease. The search included various databases. The referencing arrangements of every pertinent paper were additionally filtered for more studies. Results: 173 articles were included, thirty-nine of which met the eligibility criteria. Fifteen studies reported on the direct impact of physiotherapy on fall, while the rest examined the impacts of physiotherapy on factors that are associated with falls. Different outcomes, intervention types, and duration were used in these studies. Findings showed favorable results of physiotherapy on fall and near fall incidence, balance, gait, functional mobility, muscle strength and fear of falling. Conclusion: Physiotherapy can decrease fall incidence and fall risk in people with PD. However, the heterogeneity in the patients’ selection, intervention studies, outcome measures are chosen, time since the onset of disease, variation in intensity and duration of treatment between included studies makes the comparisons difficult. Consequently, more studies are needed on best intervention.